Effects of Neural Mobilization on Sensory Dysfunction and Peripheral Nerve Degeneration in Rats With Painful Diabetic Neuropathy - Zhu, Guan-Cheng (Phys Ther, 2022)
OBJECTIVE: This study aims to evaluate the effectiveness of neural mobilization (NM) in the management of sensory dysfunction and nerve degeneration related to experimental painful diabetic neuropathy (PDN). METHODS: This is a pre-clinical animal study performed in the streptozocin (STZ)-induced diabetic rat model. 3 groups were included; a treatment group of rats with PDN receiving NM under anesthesia (PDN-NM, n=10), a sham treatment group of rats with PDN that only received anesthesia (PDN-Sham, n=9) and a vehicle control group with nondiabetic animals (Vehicle, n=10). Rats in the PDN-NM and PDN-Sham groups received 1 treatment sessions on day-10, 12 and 14 after STZ injection, with a 48-hour rest period between sessions. Behavioral tests were performed using von Frey and Plantar tests. Evaluation for peripheral nerve degeneration was performed through measuring protein gene product 9.5-positive (PGP9.5+) intra-epidermal nerve fiber density (IENFD) in hind-paw skin biopsies. All measurements were performed by a blinded investigator. RESULTS: The behavioral tests showed that a single NM session could reduce hyperalgesia which was maintained for 48 hours. The second treatment session further improved this treatment effect, and the third session maintained it. These results suggest that it requires multiple treatment sessions to produce and maintain hypoalgesic effects. Skin biopsy analysis showed that the PGP9.5+ IENFD was higher on the experimental side of the PDN-NM group compared to the PDN-Sham group, suggesting NM may mitigate the degeneration of peripheral nerves. CONCLUSIONS: This study demonstrated that NM may be an effective method to manage experimentally induced PDN, potentially through mitigation of nerve degeneration. Further studies are needed to develop standardized protocols for clinical use. IMPACT: These findings provide neurophysiological evidence for the use of NM in PDN and can form the basis for the development of physical therapy-based programs in clinics.